Swimming through the blood stream: Stanford engineers create wireless, self-propelled medical device (Bangladesh Medical Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bmj.v43i2.21397 Bangladesh Med J. 2014 May; 43 (2): 119-120